Consideration by the court of first instance of the petitions of the participants of the court proceedings at the trial stage: some problems of theory and practice - Панасюк, О. А. (Theory and practice of jurisprudence, 2016)
The article is devoted to the investigation of the problem concerning declaration, review and permission by the court of first instance of the petitions of the participants of court proceedings at the trial stage. The investigation of the procedural value, character and nature of petitions and some kinds of petitions that can be claimed during the trial stage has been carried out; the legal mechanism of the procedural order of their declaration, review and permission by the court has been analyzed too.